Biodiversity and climate determine the functioning of Neotropical forests. Issue 12 (16th November 2017) - Poorter, Lourens; van der Sande, Masha T.; Arets, Eric J. M. M.; Ascarrunz, Nataly; Enquist, Brian; Finegan, Bryan; Licona, Juan Carlos; Martínez‐Ramos, Miguel; Mazzei, Lucas; Meave, Jorge A.; Muñoz, Rodrigo; Nytch, Christopher J.; et al.
Abstract: Aim: Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location: Neotropics. Methods: We used data from 26 sites, 201 1‐ha plots and >92, 000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results: Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions: Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.